Determinanten des Rentenzugangs: Lockt der Ruhestand oder drängt der Arbeitsmarkt? - Regina T. Riphahn; Peter Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
This paper analyses annual, age-specific retirement rates in Germany between 1971 and 1991. The time-series data show significant changes in overall and age-specific retirement behavior over the 21 year period. The literature provides two alternative explanations for the observed developments: One theory posits that employees took advantage of increasingly lenient eligibility conditions to leave the labor force and to seek early retirement (pull factors/supply side). The opposing position asserts that high unemployment caused early retirement (push factors/demand side). This study finds that institutional eligibility rules are strongly correlated with annual, age-specific retirement rates. In contrast, aggregate unemployment cannot explain the fluctuations in retirement rates over time.
Keywords: 330